Torrefaction of oil palm empty fruit bunch pellets: product yield, distribution and fuel characterisation for enhanced energy recovery - Nyakuma, Bemgba B. (Springer Science and Business Media Deutschland GmbH, 2023)
In this study, the non-oxidative torrefaction of oil palm empty fruit bunch (OPEFB) pellets was investigated from 250 to 300 °C for 30 min in a horizontal fixed bed tubular reactor. The effects of the selected conditions on the yields, distributions and fuel characteristics of the torrefaction products were examined. The mass or solid yield (MY) decreased from 68.1 to 36.2%, whereas the liquid yield (LY) and gas yield (GY) increased from 19.4–40.1% and 12.5–23.7%, respectively, due to drying, devolatilization and depolymerisation during torrefaction. Physicochemical and calorific analyses showed that the torrefied OPEFB pellets have high carbon but low oxygen contents, which accounts for the high heating values (HHV = 22.83–25.81 MJ/kg). The torrefied OPEFB pellets also exhibit lower moisture (2–4%) and volatile matter (34.38–65.31 wt.%) but high ash (4–20 wt.%) and fixed carbon (28.69–41.62 wt.%) compared to the raw pellets. The OPEFB pellet fuel properties, namely pH that ranged from 6.65 to 7.74, hydrophobicity from 100 to 23.04% and grindability from 53.66 to 108, were markedly enhanced after torrefaction at 300 °C. The LY consisted of organics (67.64–62.62%) and water (32.36–37.38%) fractions characterised by high acidity (pH = 2.89–3.22) and dark hues formed by holocellulose and lignin thermal degradation at higher torrefaction temperatures. Based on the findings, the torrefied OPEFB pellets is a highly grindable, hydrophobic, thermally stable and promising solid biofuel for firing, co-firing or substituting coal in power plants provided the existing challenges that affect global biomass supply chains are addressed in detail.